Analysis of Women's Empowerment in Improving the Quality of Female Journalists in the Indonesian Journalists Association (PWI) DKI Jakarta - Sunarti Modjo; Rudianto Rudianto; Jones Z. Rante; Pingkan L. Sompi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze women's empowerment strategies to improve the quality of female journalists within the DKI Jakarta Indonesian Journalists Association (PWI). Even though the role of women in journalism has increased, significant challenges are still faced in efforts to improve the quality and competence of female journalists. This research uses a qualitative method with a case study approach, which involves in-depth interviews with female journalists, Head of PWI DKI Jakarta, and women's empowerment experts and document analysis related to existing training and development programs. The research results show that empowering women through technical training programs, seminars, and mentoring has proven effective in improving the journalistic skills of female journalists. In addition, support from PWI DKI Jakarta in the form of professional networks, publication opportunities, and access to information resources greatly contributes to the career development of female journalists. However, gender stereotypes and lack of representation in managerial positions remain significant obstacles. The research recommends developing empowerment programs that are more focused on specific aspects such as leadership and media management and expanding the range of support to overcome existing obstacles. With a more comprehensive approach, it is hoped that the quality of female journalists can continue to be improved so that their contribution to the world of journalism can be maximized and positively impact society.